Thromboangiitis Obliterans Successfully Treated With Smoking-Cessation Instruction Including Passive Smoking Cessation - Yasutaka Yanagita; Takanori Uehara; Mizuki Momose; Masatomi Ikusaka (Annals of Internal Medicine: Clinical Cases)
A 22-year-old man presented with recurrent pain and linear redness of the lower extremities for 1 year. He smoked 20 cigarettes daily for 6 years and did not report cannabis use. He was referred to the vascular department by his primary care physician. He had stopped smoking for 6 months to treat thromboangiitis obliterans, but his symptoms were recurrent. The patient was interviewed about smoking in his living environment. His family members and his colleagues were smokers. Therefore, we advised to avoid secondhand smoke as well. Consequently, his symptoms resolved within 2 weeks. He had no relapse at follow-up after 6 months.